Ureteric foreign body following previous aorto-iliac graft - da Silva, Vitor; Taylor, Jonathan (Canadian Urological Association Journal, 2015)
Foreign bodies in the ureter are extremely rare. We report a case of an 82-year-old man who, after an incidental presentation with asymptomatic hydroureteronephrosis, had an intraureteric foreign body. The patient was managed with atraumatic endoscopic extraction of the specimen.